Review article: A primer for clinical researchers in the emergency department: Part IX. How to conduct a systematic review in the field of emergency medicine. (15th April 2019) - Long, Elliot; Craig, Simon; Babl, Franz E; Tavender, Emma; Lunny, Carole
Abstract: In this series we address important topics for emergency clinicians who either participate in research as part of their work, or use the knowledge generated by research studies. Emergency clinicians are routinely in the position of applying new evidence in clinical practice. With an ever‐increasing volume of evidence generated, this can be problematic when studies are conducted in different settings, and include different patient groups, different interventions and different outcomes. This is made even more difficult when the results of primary research studies do not agree. Systematic reviews are becoming increasingly valuable as they appraise and synthesise research findings using a clear methodology, and summarise the results of primary studies. As such, systematic reviews help translate research findings into clinical practice. This paper provides a practical starting point for understanding the steps involved in conducting a systematic review in emergency medicine and will help readers appraise the findings of systematic reviews.